ASSESSMENT OF THE CHILDREN AND ADULTS’ COVID-19 SICKNESS RATE IN CHERNIVTSI FOR THE PERIOD OF 2021-2023 - Мельничук, Лариса; Вострикова, Ірина (SWorldJournal, 2024)
The article analyzes statistical indicators of the incidence of coronavirus disease in children and adults in the city of Chernivtsi for the period 2020-2023. The results show that 74,211 residents fell ill in the city during the entire pandemic. The num